A systematic review of temporal discounting in eating disorders and obesity: Behavioural and neuroimaging findings. (December 2016) - McClelland, Jessica; Dalton, Bethan; Kekic, Maria; Bartholdy, Savani; Campbell, Iain C.; Schmidt, Ulrike
Highlights: Temporal discounting (TD) tasks can be used to explore self-regulatory control. Limited data suggest increased TD in obesity, BED and BN, data in AN are mixed. Frontostriatal neurocircuitry is implicated in TD and related to clinical outcomes. TD tasks are heterogeneous, limiting comparability and generalisability of results. TD may be multidimensional, state-related and important in treatment of ED/obesity. Abstract: Objective: Eating Disorders (ED) and obesity are suggested to involve a spectrum of self-regulatory control difficulties. Temporal discounting (TD) tasks have been used to explore this idea. This systematic review examines behavioural and neuroimaging TD data in ED and obesity. Method: Using PRISMA guidelines, we reviewed relevant articles in MEDLINE, PsycINFO and Embase from inception until 17th August 2016. Studies that reported behavioural differences in TD and/or TD neuroimaging data in ED/obesity were included. Results: Thirty-one studies were included. Limited data suggest that BN, BED and obesity are associated with increased TD, whilst data in AN are mixed. Aberrant neural activity in frontostriatal circuitry is implicated. TD tasks vary widely and TD in ED/obesity may vary according to factors such as illness stage. Conclusion: Our findings suggest altered self-regulatory control in ED and obesity. TD tasks are heterogeneous, limiting generalisability of findings. Research into whether TD is multidimensional, along with transdiagnostic neuroimaging research is needed. Assessment of TD may be useful in psychoeducation, outcome prediction and treatment of ED/obesity.